Social Media Exposure, Psychological Distress, Emotion Regulation, and Depression During the COVID-19 Outbreak in Community Samples in China - Zhang, Yu-ting; Li, Rui-ting; Sun, Xiao-jun; Peng, Ming; Li, Xu (Frontiers in Psychiatry, 2021)
The outbreak of Corona Virus Disease 2019 (COVID-19) has been a global emergency, affecting millions of individuals both physically and psychologically. The present research investigated the associations between social media exposure and depression during the COVID-19 outbreak by examining the mediating role of psychological distress and the moderating role of emotion regulation among members of the general public in China. Participants (N = 485) completed a set of questionnaires online, including demographic information, self-rated physical health and social media exposure to topics related to COVID-19. The Impact of Event Scale-Revised (IES-R), the Beck Depression Inventory-II (BDI-II), and the Emotion Regulation Questionnaire (ERQ) were utilized measure psychological distress about COVID-19, depression and emotion regulation strategies respectively. Results found that older age and greater levels of social media exposure were associated with more psychological distress about the virus (r = 0.14, p = .003; r = 0.22, p < 0.001). Results of the moderated mediation model suggest that psychological distress mediated the relationship between social media exposure and depression (β = 0.10, Boot95%CI = [0.07, 0.15]). Furthermore, expressive suppression moderated the relationship between psychological distress and depression (β = 0.10, p = 0.017). The findings are discussed in terms of the need for mental health assistance for individuals at high risk of depression, including the elderly and individuals reported greater psychological distress and those who showed preference usage of suppression, during the COVID-19 crisis.